Epsilon-near-zero enhancement of nonlinear responses from intersubband transitions in the mid-infrared - Barbet, Geoffrey (2023)
Many applications of photonics require efficient nonlinear optical interactions with low power and small footprints. However, the current needs for long interaction lengths and strong laser sources of nonlinear optical devices make them unsuitable for nanophotonic integrated optics. New materials and devices with stronger nonlinear properties have been developed using various approaches in the past few years. One of the largest nonlinear optical responses reported to date has been realized with engineered intersubband transitions in n-doped multiple quantum wells (MQWs) semiconductors. Here, this work proposes to improve further the nonlinear properties of a MQW heterostructure by tailoring its permittivity to reach near-zero values. Materials with vanishing permittivity, called epsilon-near-zero (ENZ) materials, have exotic nonlinear features which can be explored to achieve this goal. To prove this point, this work makes use of In0.53Ga0.47As/Al0.48In0.52As, designs an ultrathin multilayer structure, and couples the designed structure with metasurfaces. Unprecedented nonlinear efficiency within subwavelength propagation lengths is obtained. Such structure with strong second harmonic generation (SHG) enables efficient frequency conversion, while the tunability offered by the metasurface provides new degrees of freedom to control the amplitude, phase, and polarization of the nonlinear light.